PENERAPAN TECHNIQUE FOR ORDERS PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) UNTUK KEPUTUSAN PEMBERIAN KREDIT PADA CALON NASABAH (Studi Kasus : PT. SS Finance) - Yustinus Zai; Mesran Mesran; Berto Nadeak; Imam Saputra (STMIK Budi Darma, 2017)
The existence of credit activities in a bank or company, certainly is one of the advantages for the bank or company, including the customer. In crediting the need for an assessment as a consideration for a prospective customer before the bank decides whether to accept or reject the request of a prospective customer. This is done, considering the risk of uncollectible on the customer is quite large. In order to assist in determining whether a person is eligible to receive a loan, a decision support system is required. One method that can be used for decision support systems is to use TOPSIS. In this research will be discussed a case in finding the best prospective customer alternative based on predetermined criteria by using Techniques For Order Preference By Similarity To Ideal Solution (TOPSIS) method to calculate the eligibility of the prospective customer